The Plant Water Extract-Based Bioherbicides in Sustainable Weed Control: A Review of Experimental Studies - Edi Susilo; Hesti Pujiwati; Wismalinda Rita (UNIVED Press, Dehasen University Bengkulu, 2026)
Objective: This study aims to estimate the success rate of bioherbicides and observe their potential as a more environmentally friendly and sustainable means of weed control, particularly those based on plant water extracts, in inhibiting the growth and suppressing the germination of weeds. Methodology: This research is systematic in nature, in the form of a literature review of experiments that have been published in the last ten years. This literature search was conducted across database systems, both national and international, and the selection of articles followed the PRISMA methodology. Results: A review of research in various fields, both experimental and non-experimental, shows that plant water extracts, whether sourced from cultivated plants, weeds, medicinal plants, or aromatic plants, can inhibit weed sprouts, root growth, shoots, and biomass, and this can be done for various types of weeds. Experimental studies show that bioherbicides derived from aqueous extracts of various weed types, when grown to optimal levels, actively participate in regulating their growth patterns. Findings: Most studies show a tendency toward an increase in root shoot extracts that have a modulating effect, along with an increase in the concentration of extracts that have an inhibitory effect. Novelty: This review presents a comprehensive, experimental-based synthesis approach specifically for the use of water extracts as environmentally friendly bioherbicides in solvents. Originality: This article synthesizes aspects of extract sources, allelopathy mechanisms, and factors determining effectiveness to formulate recommendations for the application and development of sustainable bioherbicides. Conclusion: Bioherbicides derived from aquatic plant extracts have the potential to serve as an alternative, effective, and environmentally friendly technology for weed control. However, this still requires further formulation standards and field validation. Document type: Literature review.